Community health workers in rural Punjab, India: analyzing their role, expectations and challenges. Issue 2 (11th March 2021) - Mahajan, Niharika; Kaur, Baljit
Abstract : Purpose: This study aimed to analyze the role of community health workers (CHWs) called accredited social health activists (ASHAs) in improving maternal health outcomes in the rural community of Punjab, India. The study also examined the expectations of these workers from the community and identified the problems faced by them in carrying out their roles. Design/methodology/approach: Using multistage sampling, a total of 28 villages were selected from seven districts of Punjab, and from these selected villages, a total of 57 ASHAs working as the interface between the rural community and the public health system and 420 women who had delivered a baby were interviewed. Findings: Desire to earn money was the most prominent reason for joining the community work program, but ASHAs felt overburdened and underpaid compared to their work commitments. Not only was the incentive paid to these workers was insufficient and irregular but they also suffered at the hands of medical staff at public hospitals. Originality/value: While exploring the problems experienced by the CHWs, this study recommends opting for a mix of monetary and nonmonetary incentives for acknowledging the work of CHWs. The study is the first of its kind for the state of Punjab battling with a worsening maternal mortality rate (MMR).